Impact of transfer of technology in cashew cultivation - R. Venkattakumar,; T.N. Raviprasad,; M.G. Nayak, (Journal of Agricultural Extension Management, 2025)
The National Research Center for Cashew (NRCC), Puttur, is responsible for the development of improved cashew cultivation practices and employs various modes of technology transfer in dissemination of these technologies. These efforts include laying out demonstration plots on farmers' fields, organizing thematic campaigns on various themes (viz., soil and water conservation measures, plant protection measures, pruning in cashew and high density planting in cashew) and organizing cashew days/cashew field days. The aim of organizing such programmes is to educate the farmers on recommended cashew cultivation practices. However the actual impact of these modes of transfer of technology in terms of knowledge and adoption level of the cashew growers is not known